Platinum or platinum alloy supported carbon catalyst and producing method thereof, membrane electrode assembly for solid polymer type fuel cell using platinum or platinum alloy supported carbon catalyst and solid polymer type fuel cell
By uniformly distributing platinum or platinum alloy particles in the carbon support in a two-stage method in a solid polymer fuel cell, the problems of reducing activity and durability of platinum or platinum alloy support carbon catalysts in the prior art are solved, and a catalyst with high initial activity and excellent durability is achieved.
Patent Information
- Application Number
- JP2023171974
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-03
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-10-03
AI Technical Summary
In the prior art, platinum or platinum alloy supports carbon catalysts with reduced activity and durability problems in solid polymer fuel cells, especially catalyst degradation due to ionic contamination and aggregation of platinum particles.
By uniformly distributing platinum or platinum alloy particles inside and outside the particles of the carbon support, a two-stage method is adopted: firstly support the platinum particles in the particles of the carbon support by infiltration and heat treatment, and then support the platinum particles outside the carrier by liquid phase reduction.
The high initial activity and excellent durability of the carbon catalyst are achieved by platinum or platinum alloys, and catalyst degradation caused by ionic contamination and aggregation are avoided by regulating the distribution and size of platinum particles inside and outside the support.
Smart Images

Figure 2025062748000001 
Figure 2025062748000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly active and highly durable platinum or platinum alloy supported carbon catalyst for polymer electrolyte fuel cells, in which platinum particles or platinum alloy particles are supported inside and outside the pores of a carrier. [Background technology]
[0002] In recent years, decarbonization and carbon neutrality have been promoted as measures to address energy and environmental issues, and the use of hydrogen as a clean energy source to replace chemical fuels has been attracting attention. Fuel cells generate electricity by chemically reacting hydrogen with oxygen, and because they do not emit carbon dioxide, a greenhouse gas, they are expected to be a new power generation system that contributes to carbon neutrality. Among these, polymer electrolyte fuel cells (PEFCs), one type of fuel cell, use a solid polymer ion-conducting membrane as the electrolyte layer and have a low operating temperature of room temperature to 100°C, allowing the device to be miniaturized. As a result, their practical use as a power source for electric vehicles and stationary power sources is being promoted.
[0003] A polymer electrolyte fuel cell has a cell stack structure in which multiple single cells, each of which has a membrane electrode assembly (MEA) sandwiched between separators, are stacked. The MEA has a structure in which an electrolyte layer is sandwiched between two electrode catalyst layers made of an electrode catalyst and an electrolyte polymer (ionomer).
[0004] In the MEA, the following electrochemical reactions take place to generate electricity. First, hydrogen supplied as fuel is oxidized by the electrode catalyst in the fuel electrode (anode) side electrode catalyst layer to become protons and electrons. Next, the generated protons pass through an electrolyte layer made of an ion-conductive electrolyte, while the electrons pass through an external circuit to reach the oxygen electrode (cathode) side electrode catalyst layer. The protons and electrons that reach the cathode side electrode catalyst layer react with oxygen supplied to the cathode side to generate water. When the electrons generated at the anode side electrode move to the cathode side electrode via the external circuit, they are used as electrical energy.
[0005] Conventional electrode catalysts use platinum or platinum alloy-supported carbon catalysts, which are made by supporting nanoparticles of platinum (Pt) or platinum alloys on a highly electronically conductive carbon black carrier. The platinum or platinum alloy-supported carbon catalysts use high-specific surface area carbon to support platinum particles or platinum alloy particles in a highly dispersed state without agglomeration, which increases the electrode reaction area on the surface of the platinum particles or platinum alloy particles, allowing sufficient activity to be achieved with a small amount of platinum or platinum alloy support.
[0006] In order to popularize fuel cell vehicles (FCVs) toward achieving carbon neutrality, there is a demand for the development of cathode catalysts for polymer electrolyte fuel cells (PEFCs) that are highly efficient and capable of high-load operation.
[0007] Cited Document 1 describes a platinum-supported carbon catalyst supported on solid-structure carbon such as furnace black or acetylene black, whose particles have dense interiors.
[0008] Cited Document 2 discloses an electrode catalyst in which platinum particles are supported within the pores of a porous hollow carbon support such as Ketjen Black. It is mentioned that by supporting platinum particles within the pores, the adsorption of ionomer onto the platinum particle surface is suppressed, and a decrease in the effective reaction surface area of the platinum particles can be prevented. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2007-112660 A [Patent Document 2] JP 2013-109856 A Summary of the Invention [Problem to be solved by the invention]
[0010] For example, platinum-supported carbon catalysts supported on solid-structure carbon with dense particle interiors, such as furnace black or acetylene black, have excellent material transport properties because the platinum particles are supported on the surface of the support, and the reaction progresses easily when the reactant gas comes into contact with the platinum particles. However, because the platinum particles are on the surface of the support, there are problems with reduced activity due to ionomer poisoning and catalyst deterioration due to platinum particle aggregation (sintering).
[0011] On the other hand, platinum-supported carbon catalysts, which use porous carbon such as Ketjen black as a support and support platinum particles inside the pores, are also widely used. Because the platinum particles are supported inside the pores of the support, ionomer poisoning is reduced and the decrease in catalytic activity is suppressed. However, although the activity of platinum particles supported inside the pores is high, there is a problem that the access of protons and reactant gases is limited.
[0012] Therefore, a method is required for supporting platinum particles or platinum alloy particles in the pores of a carrier at a desired ratio between the inside and outside of the pores. If platinum particles or platinum alloy particles can be supported in the pores of a carrier at a desired ratio between the inside and outside of the pores, it will be possible to provide catalytically active components with different functions by selectively supporting them in the inside and outside of the pores, thereby adjusting the performance.
[0013] An object of the present invention is to provide a platinum or platinum alloy supported carbon catalyst having high initial activity and excellent durability by selectively supporting platinum particles or platinum alloy particles inside and outside the pores of a carbon support. [Means for solving the problem]
[0014] The inventors have discovered that by adopting a two-step loading process, which comprises a step of loading platinum particles or platinum alloy particles inside the pores of a carbon support by an impregnation method and a step of loading platinum particles outside the pores of the carbon support by a liquid phase reduction method, it is possible to control the loading amount and particle size of the platinum particles or platinum alloy particles loaded inside and outside the pores.
[0015] That is, the present invention provides A platinum or platinum alloy supported carbon catalyst in which platinum particles or platinum alloy particles are supported on mesoporous carbon, The platinum or platinum alloy loading rate in the catalyst is 30% to 70% by weight based on the total weight of the catalyst; the total weight of the platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon is 60 to 90% of the total weight of the platinum particles or platinum alloy particles; an average particle size D1 of platinum particles or platinum alloy particles supported within the pores of the mesoporous carbon is equal to or larger than an average particle size D2 of platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon; The average particle size D1 and the average particle size D2 are independently 2 nm or more and 8 nm or less. The present invention relates to a platinum or platinum alloy supported carbon catalyst.
[0016] In the above configuration, the average particle size D1 is 2.5 nm or more and 8 nm or less, The average particle size D2 is 2.3 nm or more and 7.3 nm or less, D1 / D2 may be set to be 1.0 to 2.1.
[0017] The manufacturing method of the present invention further comprises the steps of: A step of impregnating a mesoporous carbon support with an aqueous solution containing a platinum compound; a step of drying the mesoporous carbon support impregnated with the platinum compound-containing aqueous solution obtained in the above step under reduced pressure; a step of supporting platinum in the pores of the mesoporous carbon support, the step including a step of heat-treating the mesoporous carbon support dried under reduced pressure in a reducing atmosphere; a step of suspending the mesoporous carbon support having platinum supported in the pores after the intrapore supporting step in an aqueous solution; mixing the suspension with an aqueous solution containing a platinum compound and a liquid containing a reducing agent to reduce the platinum compound; The present invention relates to a method for producing a platinum-supported carbon catalyst comprising the steps of:
[0018] The in-pore supporting step includes: A step of adding and mixing an aqueous solution of dinitrodiamine platinum nitric acid to a mesoporous carbon support to obtain a platinum-supported carbon slurry; drying the obtained slurry at a predetermined temperature under reduced pressure to obtain a dry product; a step of reducing dinitrodiamine platinum by heat treatment in a reducing atmosphere; and a step of growing platinum particles by firing in an inert gas atmosphere (firing temperature T1), The outside-pore supporting step includes: The mesoporous carbon support having platinum supported in the pores after the intrapore supporting step is suspended in an aqueous nitric acid solution; a step of heating and stirring the suspension, an aqueous dinitrodiamine platinum nitric acid solution, and a liquid containing L-ascorbic acid at 80°C to 100°C for 30 minutes to 5 hours to support platinum particles on the outside of the pores of the carbon support; a step of filtering out the platinum-supported carbon having platinum particles supported outside the pores of the carbon support in the above step, washing the carbon support, drying the carbon support, and then calcining the carbon support in an inert gas atmosphere (calcination temperature T2) to grow platinum particles; The above may be included.
[0019] In the above manufacturing method, a step of adding an aqueous solution containing a compound of a metal to be alloyed with the platinum to the platinum-supported carbon catalyst and mixing them to obtain a slurry; and a step of heating and drying the obtained slurry under reduced pressure to obtain a dry solid. The method may further include an alloying step of performing a pretreatment firing of the dried product in a reducing atmosphere, followed by firing in an inert gas atmosphere to perform an alloying treatment.
[0020] In the above manufacturing method, The average particle size D1 of the platinum particles and the average particle size D2 of the platinum particles may be controlled by setting the firing temperature T1 and the firing temperature T2 to predetermined temperatures, respectively. Effect of the Invention
[0021] According to the present invention, by selectively supporting platinum particles or platinum alloy particles inside and outside the pores of a carbon support, it is possible to provide a platinum or platinum alloy supported carbon catalyst having high initial activity and excellent durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The production method of the present invention will first be described.
[0023] The production method of the present invention comprises the steps of: A step of impregnating a mesoporous carbon support with an aqueous solution containing a platinum compound; a step of drying the mesoporous carbon support impregnated with the platinum compound-containing aqueous solution obtained in the above step under reduced pressure; a step of supporting platinum in the pores of the mesoporous carbon support, the step including a step of heat-treating the mesoporous carbon support dried under reduced pressure in a reducing atmosphere; a step of suspending the mesoporous carbon support having platinum supported in the pores after the intrapore supporting step in an aqueous solution; mixing the suspension with an aqueous solution containing a platinum compound and a liquid containing a reducing agent to reduce the platinum compound; The present invention relates to a method for producing a platinum-supported carbon catalyst, comprising the steps of:
[0024] The manufacturing method of the present invention further comprises the steps of: In the above manufacturing method, The in-pore supporting step includes: A step of adding and mixing an aqueous solution of dinitrodiamine platinum nitric acid to a mesoporous carbon support to obtain a platinum-supported carbon slurry; drying the obtained slurry at a predetermined temperature under reduced pressure to obtain a dry product; a step of reducing dinitrodiamine platinum by heat treatment in a reducing atmosphere; and a step of growing platinum particles by firing in an inert gas atmosphere (firing temperature T1), The outside-pore supporting step includes: The mesoporous carbon support having platinum supported in the pores after the intrapore supporting step is suspended in an aqueous nitric acid solution; a step of heating and stirring the suspension, an aqueous dinitrodiamine platinum nitric acid solution, and a liquid containing L-ascorbic acid at 80°C to 100°C for 30 minutes to 5 hours to support platinum particles on the outside of the pores of the carbon support; a step of filtering out the platinum-supported carbon having platinum particles supported outside the pores of the carbon support in the above step, washing the carbon support, drying the carbon support, and then calcining the carbon support in an inert gas atmosphere (calcination temperature T2) to grow platinum particles; The above may be included.
[0025] When a catalytically active component (e.g., platinum) is supplied in a solution and supported on a carrier, this is called impregnation, and the catalytically active component (e.g., platinum) is easily supported in the pores of the carrier. The production method of the present invention employs a two-stage supporting process in which the catalytically active component (e.g., platinum) is supported in the pores of the carrier by the impregnation method, and then the catalytically active component (e.g., platinum) is supported outside the carrier pores by the liquid phase reduction method.
[0026] As the platinum-containing aqueous solution, an aqueous dinitrodiamine platinum nitric acid solution, an aqueous chloroplatinic acid solution, or the like can be used.
[0027] Mesoporous carbon is used as the carrier. Mesoporous carbon is a carbon material having pores on the order of nanometers. Mesoporous carbons having various pore volumes and specific surface areas can be used for the platinum or platinum alloy supported carbon catalyst of the present invention.
[0028] In the outer pore loading step, L-ascorbic acid, citric acid, etc. are used as reducing agents. In the outside-pore supporting step, an alcohol-based solvent may be added to the aqueous nitric acid solution as a dispersion solvent. As the alcohol-based solvent, ethanol, 2-propanol, etc. can be used.
[0029] The inert gas may be nitrogen, argon, or the like.
[0030] Hereinafter, the platinum particles or platinum alloy particles supported within the pores of the support will be referred to as first platinum particles or platinum alloy particles, and the platinum particles or platinum alloy particles supported outside the pores of the support will be referred to as second platinum particles or platinum alloy particles.
[0031] The process of supporting platinum in the pores of the mesoporous carbon support is, for example, as follows: A dinitrodiamine platinum nitric acid aqueous solution is added to the mesoporous carbon support and mixed to form a platinum-supported carbon slurry, which is then dried at a predetermined temperature under reduced pressure to obtain a dry solid. The resulting dry solid is heat-treated in a reducing atmosphere to reduce the dinitrodiamine platinum, and then fired (at firing temperature T1) in an inert gas (e.g., nitrogen) atmosphere to grow the platinum particles, thereby preparing carbon supporting first platinum particles in the pores.
[0032] The outside-pore supporting step is, for example, as follows. The carbon carrying the first platinum particles in the pores is suspended in an aqueous nitric acid solution, and the suspension is mixed with an aqueous dinitrodiamine platinum nitric acid solution, ethanol, and L-ascorbic acid. Next, the mixture is heated and stirred at 80°C to 100°C for 30 minutes to 5 hours. For example, the mixture is heated at 90°C for 1 hour using a reflux reactor to reduce dinitrodiamine platinum in the liquid phase, and platinum particles are supported outside the pores of the carbon support. The platinum-supported carbon having the second platinum particles supported outside the pores of the carbon support is filtered out, then washed and dried, and then calcined in an inert gas atmosphere (calcination temperature T2) to grow the platinum particles, thereby preparing a platinum-supported carbon catalyst in which platinum particles are selectively supported inside and outside the pores of the carbon support.
[0033] After the above-mentioned filtration, washing, and drying, but before calcination in an inert gas atmosphere (calcination temperature T2), residual reducing agent (L-ascorbic acid) that was not completely removed by washing may be thermally decomposed and removed by heat treatment in an oxygen-free atmosphere. An example of the oxygen-free atmosphere is 4.0% hydrogen / nitrogen.
[0034] The production method of the present invention includes the steps of: adding an aqueous solution containing a compound of a metal to be alloyed with the platinum to the platinum-supported carbon catalyst and mixing them to obtain a slurry; and heating and drying the obtained slurry under reduced pressure to obtain a dry product. The method may further include an alloying step of performing a pretreatment firing of the dried product in a reducing atmosphere, followed by firing in an inert gas atmosphere to perform an alloying treatment.
[0035] For example, a cobalt nitrate aqueous solution obtained by dissolving cobalt (II) nitrate hexahydrate in water is added to the platinum-supported carbon catalyst prepared by the above method, and the mixture is mixed using a kneader to obtain a slurry. The obtained slurry is dried, for example, at 80°C to 250°C under reduced pressure for 1 to 15 hours using a vacuum dryer to obtain a dried product. The dried product is reduced in an atmosphere furnace in a mixed atmosphere of hydrogen / nitrogen at 200°C to 600°C for 1 to 5 hours, and then calcined in an inert gas flow at 700°C to 900°C for 0.5 to 5 hours to perform an alloying treatment. Thereafter, excess cobalt is removed by acid washing. The product is then filtered, washed, and dried to obtain a platinum-cobalt supported carbon catalyst.
[0036] In addition, in the manufacturing method of the present invention, the firing temperature T1 and the firing temperature T2 may be set to predetermined temperatures, respectively, to control the average particle size D1 of the platinum particles and the average particle size D2 of the platinum particles.
[0037] The firing temperature T1 and the firing temperature T2 can be, for example, 500° C. to 1000° C. By firing at 500° C. to 1000° C., the platinum particles can be made to have a predetermined size.
[0038] Next, the catalyst of the present invention is A platinum or platinum alloy supported carbon catalyst in which platinum particles or platinum alloy particles are supported on mesoporous carbon, The platinum or platinum alloy loading rate in the catalyst is 30% to 70% by weight based on the total weight of the catalyst; the total weight of the platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon is 60 to 90% of the total weight of the platinum particles or platinum alloy particles; an average particle size D1 of platinum particles or platinum alloy particles supported within the pores of the mesoporous carbon is equal to or larger than an average particle size D2 of platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon; The average particle size D1 and the average particle size D2 are independently 2 nm or more and 8 nm or less. The present invention relates to a platinum or platinum alloy supported carbon catalyst.
[0039] The platinum or platinum alloy loading rate in the platinum or platinum alloy-supported carbon catalyst can be determined, for example, by dissolving the metal components contained in the platinum particles or platinum alloy particles from the platinum or platinum alloy-supported carbon catalyst using aqua regia, and then quantifying the metal ions in the solution using an inductively coupled plasma (ICP) optical emission spectrometer.
[0040] The platinum or platinum alloy loading rate in the platinum or platinum alloy supported carbon catalyst is 30% to 70% by weight based on the total weight of the catalyst. By setting the loading density of platinum particles or platinum alloy particles within the above range, the thickness of the electrode catalyst layer can be controlled to be suitable for proton transfer, gas diffusion, and drainage of generated water during the formation of the electrode catalyst layer.
[0041] The platinum or platinum alloy loading rate in the platinum or platinum alloy supported carbon catalyst is preferably 35% to 60% by weight based on the total weight of the catalyst, and more preferably 40% to 55% by weight based on the total weight of the catalyst.
[0042] The total weight of the platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon relative to the total weight of the platinum particles or platinum alloy particles supported on the mesoporous carbon (i.e., the total weight of the platinum particles or platinum alloy particles supported inside and outside the pores of the mesoporous carbon) is 60 to 90%. By supporting the platinum particles or platinum alloy particles inside the pores of the carbon support, the contact area with the ionomer can be reduced, which is expected to reduce the poisoning of the platinum particles or platinum alloy particles by the sulfonic acid groups of the ionomer and to show high initial activity. However, from the viewpoint of material transport properties such as protons and reaction gases, it is necessary to appropriately adjust the support ratio inside the pores and outside the pores, and the total weight of the platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon relative to the total weight of the platinum particles or platinum alloy particles supported on the mesoporous carbon is 60 to 90%.
[0043] The total weight of platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon is preferably 80% or less, and more preferably 70% or less, of the total weight of platinum particles or platinum alloy particles supported on the mesoporous carbon.
[0044] The catalyst of the present invention is The average particle size D1 of the platinum particles or platinum alloy particles is 2.5 nm or more and 8 nm or less, The average particle size D2 of the platinum particles or platinum alloy particles is 2.3 nm or more and 7.3 nm or less. , D1 / D2 is 1.0 to 2.1. This may be done.
[0045] In a fuel cell operating environment accompanied by potential fluctuations, platinum particles with small diameters are preferentially dissolved and redeposited on the surface of platinum particles with large diameters, causing the platinum particles to become coarse and the catalytically active components to deteriorate. In order to prevent platinum particles or platinum alloy particles supported in the pores, which are not easily affected by ionomer poisoning and exhibit high activity, from dissolving from the inside of the pores to the outside of the pores, it is preferable that the average particle size D1 is greater than or equal to the average particle size D2. Here, the average particle size D1 is the average particle size of platinum particles or platinum alloy particles supported in the pores of the mesoporous carbon, and the average particle size D2 is the average particle size of platinum particles or platinum alloy particles supported outside the pores.
[0046] It is more preferable that the average particle size D1 of the platinum particles or platinum alloy particles (platinum particles or platinum alloy particles inside the pores) is larger than the average particle size D2 of the platinum particles or platinum alloy particles (platinum particles or platinum alloy particles outside the pores).
[0047] D1 / D2 can be set to 1.0 to 2.1, and is preferably set to 1.1 to 1.8.
[0048] By having the average particle size of the platinum particles or platinum alloy particles in the above range, both initial activity and durability can be achieved. If the average particle size of the platinum particles or platinum alloy particles is smaller than the above range, the active surface area will be large and initial activity will be improved, but the platinum particles or platinum alloy particles will be easily coarsened due to dissolution and reprecipitation, resulting in a decrease in durability. On the other hand, if the average particle size of the platinum particles or platinum alloy particles is larger than the above range, coarsening due to dissolution and reprecipitation and the movement and aggregation of the platinum particles or platinum alloy particles will not easily proceed, but the initial activity will decrease due to the low active surface area of the platinum particles or platinum alloy particles.
[0049] By selectively supporting platinum particles or platinum alloy particles supported inside the pores, which suppress ionomer poisoning and show high activity, and platinum particles or platinum alloy particles supported outside the pores, which have excellent material transport properties, the performance can be adjusted to exhibit high initial activity. Furthermore, by making the average particle size of the platinum particles or platinum alloy particles supported inside the pores larger than that of the platinum particles or platinum alloy particles supported outside the pores, deterioration due to elution of the platinum particles or platinum alloy particles in the operating environment is suppressed, and durability is improved.
[0050] The catalytically active component contained in the platinum or platinum alloy supported carbon catalyst of the present invention is platinum (Pt) or a platinum alloy.The platinum alloy may include one or more additional metals forming the platinum alloy, such as titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), gallium (Ga), yttrium (Y), zirconium (Zr), molybdenum (Mo), lanthanum (La), cerium (Ce), gadolinium (Gd), hafnium (Hf), tantalum (Ta), ruthenium (Ru), iridium (Ir), palladium (Pd), osmium (Os), and rhodium (Rh).When the platinum alloy particles contained in the fuel cell electrode catalyst of the present invention contain the above-mentioned catalytic metal, an electrode catalyst having high activity and high durability can be obtained. EXAMPLES
[0051] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0052] Example 1 1. Preparation of carbon with platinum supported in pores (first platinum particle support step in pores) As a support, pore volume 3.5 cm 3 / g mesoporous carbon was used. 128.0 g of dinitrodiamine platinum nitric acid aqueous solution containing 8.3 wt% platinum was added to 31.8 g of mesoporous carbon support, and mixed for 30 minutes using a kneader to obtain a platinum-supported carbon slurry. The obtained slurry was dried at 200 ° C under reduced pressure using a vacuum dryer for 12 hours to obtain a dried product. The dried product was then heat-treated in an atmospheric furnace at 200 ° C for 2 hours under a 4.0% hydrogen / nitrogen flow to reduce the dinitrodiamine platinum. Then, the product was baked for 1 hour at a baking temperature T1 (medium) of 600 ° C under nitrogen flow to grow platinum particles, and carbon with 25 wt% of first platinum particles supported in the pores was obtained.
[0053] 2. Preparation of carbon catalyst with platinum supported inside and outside of pores (second platinum particle supporting step outside of pores) 10.0 g of carbon carrying 25 wt% first platinum particles in the pores was suspended in 150 g of 0.1 M nitric acid, to which 48.1 g of dinitrodiamine platinum nitric acid aqueous solution containing 8.3 wt% platinum, 4.0 g of ethanol, and 7.5 g of L-ascorbic acid were added to prepare a mixture. This mixture was heated at 90°C for 1 hour using a reflux reactor to reduce dinitrodiamine platinum in the liquid phase, and platinum particles were supported outside the carbon support pores. The mixture was then allowed to cool to room temperature, and the platinum-on-carbon in the mixture was filtered off, then washed and dried at 60° C. for 12 hours. After drying, the substrate was heat-treated in an atmospheric furnace under a 4.0% hydrogen / nitrogen flow at 200° C. for 2 hours to thermally decompose the adhering reducing agent (L-ascorbic acid) residue. Next, the mixture was calcined for 1 hour at a calcination temperature T2 (outside) of 600° C. under a nitrogen flow to grow platinum particles supported outside the pores. As a result, a carbon catalyst was obtained with 47 wt% of first and second platinum particles supported inside and outside the pores. The total weight of the second platinum particles supported outside the pores of the mesoporous carbon was 63% of the total weight of the first and second platinum particles supported on the mesoporous carbon.
[0054] Example 2 A platinum-supported carbon catalyst was obtained in the same manner as in Example 1, except that the nitrogen calcination temperature T1 (medium) in the step of supporting the first platinum particles in the pores was changed from 600° C. to 700° C.
[0055] Example 3 A platinum-supported carbon catalyst was obtained in the same manner as in Example 1, except that the nitrogen calcination temperature T1 (medium) in the step of supporting the first platinum particles in the pores was changed from 600° C. to 900° C.
[0056] Example 4 A platinum-supported carbon catalyst was obtained in the same manner as in Example 1, except that the nitrogen calcination temperature T1 (medium) in the step of supporting the first platinum particles in the pores was changed from 600° C. to 1000° C.
[0057] Example 5 The carrier used had a pore volume of 4.5 cm 3 A platinum-supported carbon catalyst was obtained in the same manner as in Example 1, except that the carbon carrier was changed to mesoporous carbon having a molecular weight of 1.0 to 1.0 g.
[0058] Example 6 To 5.02 g of the carbon catalyst carrying platinum inside and outside the pores of Example 1, an aqueous solution of cobalt nitrate in which 2.48 g of cobalt nitrate (II) hexahydrate was dissolved in 5.18 g of water was added, and the mixture was mixed for 30 minutes using a kneader to obtain a slurry. The obtained slurry was dried for 12 hours at 200°C under reduced pressure using a vacuum dryer to obtain a dried product. This dried product was reduced for 2 hours at 200°C in a 4.0% hydrogen / nitrogen flow in an atmospheric furnace, and then baked for 1 hour at 800°C in a nitrogen flow to perform an alloying treatment. Thereafter, in order to remove excess cobalt by acid washing, 80 g of 1M nitric acid was added, and the mixture was heated at 90°C for 1 hour, and allowed to cool to room temperature, after which the black powder was filtered out, washed, and dried at 80°C for 12 hours. As a result, 5.28 g of a platinum-cobalt supported carbon catalyst was obtained.
[0059] Comparative Example 1 Pore volume 3.5cm 354.2g of dinitrodiamine platinum nitric acid solution containing 8.3wt% platinum was added to 10.0g of mesoporous carbon support of 10.0g / g, and mixed for 30 minutes using a kneader to obtain a platinum-supported carbon slurry. The obtained slurry was dried at 200°C under reduced pressure for 12 hours using a vacuum dryer to obtain a dried product. The dried product was then heat-treated in an atmospheric furnace at 200°C for 2 hours under a 4.0% hydrogen / nitrogen flow to reduce the dinitrodiamine platinum. The platinum particles were then grown by baking at 200°C for 2 hours under a nitrogen flow. As a result, carbon was obtained that supported 31wt% of the first platinum particles in the pores. The same procedure was repeated to 12.0 g of carbon with 31 wt% of first platinum particles supported within the pores, followed by adding 43.6 g of an aqueous solution of dinitrodiamineplatinum nitric acid containing 8.3 wt% platinum, and kneading, drying, reduction heat treatment, and calcination to obtain a carbon catalyst with 47 wt% of first platinum particles supported within the pores.
[0060] Comparative Example 2 Pore volume 3.5cm 3 10.0 g of mesoporous carbon support with a molecular weight of 100 / g was suspended in 400 g of 0.1 M nitric acid, to which 106.6 g of dinitrodiamine platinum nitric acid solution containing 8.3 wt% platinum, 10.3 g of ethanol, and 16.0 g of L-ascorbic acid were added to prepare a mixture. This mixture was heated at 90°C for 1 hour using a reflux reactor to reduce dinitrodiamine platinum in the liquid phase, and platinum particles were supported outside the pores of the carbon support. The mixture was then allowed to cool to room temperature, and the platinum-on-carbon in the mixture was filtered off, then washed and dried at 60° C. for 12 hours. After drying, the substrate was heat-treated in an atmospheric furnace under a 4.0% hydrogen / nitrogen flow at 200° C. for 2 hours to thermally decompose the adhering reducing agent (L-ascorbic acid) residue. Next, the catalyst was calcined at 200° C. for 2 hours under a nitrogen flow to grow the platinum particles supported outside the pores. As a result, a carbon catalyst was obtained that supported 47 wt % of second platinum particles outside the pores.
[0061] The platinum or platinum alloy supported carbon catalysts of the Examples and Comparative Examples were evaluated for the following physical properties. The results are shown in Table 1.
[0062] [Measurement of particle size distribution of platinum particles or platinum alloy particles in platinum or platinum alloy supported carbon catalyst] The particle size distribution of platinum particles or platinum alloy particles was measured using CuKα radiation as a radiation source and a small angle scattering measurement device (Nano-Viewer manufactured by Rigaku) under the following measurement conditions.
[0063] Small-angle X-ray scattering measurement (SAXS) measurement conditions Tube:CuKα ray Output: 40kV-30mA Slits: 1st slit 0.4mm, 2nd slit 0.2mm, 3rd slit 0.45mm Measurement method: Transmission method Detector: HyPix-3000 Camera length: 680mm Exposure time: 15 min Temperature: room temperature
[0064] [Measurement of the metal specific surface area of platinum particles or platinum alloy particles of platinum or platinum alloy supported carbon catalyst] The metal specific surface area of platinum particles or platinum alloy particles is measured using a metal dispersion measuring device (micrometer). The measurement was performed using a pulse method with carbon monoxide gas using a Rotrack-Bel BELMETAL3). The metal specific surface area of the catalyst particles was determined from the amount of carbon monoxide adsorbed.
[0065] [Measurement of the BET specific surface area of the carbon support of platinum or platinum alloy supported carbon catalyst] BET specific surface area (m 2 For the specific surface area (g), an automatic specific surface area / pore distribution measuring device (Microtrack-Bell BELSORP-mini2) was used to obtain a nitrogen adsorption isotherm by the gas adsorption method using nitrogen gas, and the specific surface area was determined by the multipoint method based on the BET method.
[0066] [Table 1]
[0067] In Example 1, the firing temperatures T1 (middle) and T2 (outside) were both 600°C, and the average particle size D1 of the first platinum particles inside the pores and the average particle size D2 of the second platinum particles outside the pores were 3.5 nm and were approximately the same size.
[0068] In Examples 2 to 4, the firing temperature T1 (middle) was higher than T2 (outside), and the average particle size D1 of the first platinum particles inside the pores was 3.8 to 7.1 nm, while the average particle size D2 of the second platinum particles outside the pores was 3.4 to 3.5 nm, with the average particle size D1 of the first platinum particles inside the pores being larger.
[0069] Example 5 uses mesoporous carbon having a pore volume different from that of Examples 1 to 4. As in Example 1, by treating at firing temperatures T1 (middle) and T2 (outer) of 600°C, the average particle size D1 of the first platinum particles inside the pores and the average particle size D2 of the second platinum particles outside the pores were 3.1 nm, which were approximately the same size.
[0070] In Example 6, the platinum-cobalt supported carbon was adjusted so that the average particle size D1 of the first catalyst particles inside the pores and the average particle size D2 of the second catalyst particles outside the pores were 4.4 nm, which were approximately the same size.
[0071] In Comparative Example 1, the platinum-supported carbon catalyst was prepared by repeating the intrapore supporting step by the impregnation method twice. The average particle size D1 of the first platinum particles in the pores was 3.9 nm.
[0072] In Comparative Example 2, a platinum-supported carbon catalyst was prepared by an outside-pore supporting step using a liquid-phase reduction method. The average particle size D2 of the second platinum particles outside the pores was 3.8 nm.
[0073] The metal specific surface area of the examples and comparative examples is 57 to 100 m 2 g -1 The BET specific surface area of the examples and comparative examples was 290 to 630 m 2 g -1 It was.
[0074] For the platinum or platinum alloy supported carbon catalysts of the examples and comparative examples, membrane electrode assemblies for evaluating single cells of polymer electrolyte fuel cells were fabricated by the following method.
[0075] 1. Electrode Preparation 0.8 g of platinum or platinum alloy supported carbon catalyst of each Example and Comparative Example, 4.16 g of pure water, 1.60 g of ionomer (Nafion DE2020CS manufactured by Chemours), 2.43 mL of 2-propanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 1.88 mL of 1-propanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 0.72 mL of propylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and dispersed by a planetary ball mill for 1 hour, and then degassed by a mixer for 5 minutes to obtain a cathode catalyst slurry. This electrode catalyst slurry was applied to one side of a PTFE sheet (Naflon (registered trademark) sheet manufactured by Nichias Corporation, thickness 200 μm) using a doctor blade, and dried under vacuum at 120 ° C. for 60 minutes to form a cathode catalyst layer on the PTFE sheet.
[0076] For the anode catalyst layer, FC-I2 (IFPC40-II manufactured by Ishifuku Kinzoku Kogyo), which is the reference catalyst of the Catalysis Society of Japan's Fuel Cell Related Catalyst Research Group, was used.
[0077] 2. Fabrication of MEAs A solid polymer electrolyte membrane (Nafion NR-211, 200mm x 200mm square, manufactured by Chemours) was sandwiched between the two previously prepared PTFE sheets with the electrode catalyst layer formed thereon, and the two sheets were hot pressed at 130°C for 10 minutes at a pressure of 1.5K / N using a precision heating and pressing device (CYPM, manufactured by Shinto Kogyo) and, after cooling, the PTFE sheet alone was peeled off to obtain a joint in which the electrode catalyst layer was transferred to the solid polymer electrolyte membrane. At this time, the transfer rate of the electrode catalyst layer from the PTFE sheet to the solid polymer electrolyte was 100%, and the platinum weight per 1cm2 of the electrode catalyst layer area on one side of the solid polymer electrolyte membrane was 0.30mg.
[0078] Next, the previously prepared assembly was sandwiched between two gas diffusion layers (GDL 28BC manufactured by SGL, a square of 100 mm × 100 mm), and a sealing material (Naflon (registered trademark) sheet manufactured by Nichias Corporation, a laminate of 150 μm and 80 μm thick sheets) was placed on the outer periphery of the electrode catalyst layer and the gas diffusion layer to form an MEA.
[0079] Thereafter, a gold-plated current collector with gas flow channels was placed on the fabricated MEA, which was then clamped between stainless steel end plates and clamped to a specified surface pressure to obtain a single cell of a polymer electrolyte fuel cell.
[0080] The MEAs using the platinum or platinum alloy supported carbon catalysts of the respective Examples and Comparative Examples were subjected to the following power generation evaluation. The results are shown in Table 2.
[0081] [Measurement of initial activity of MEA using platinum or platinum alloy supported carbon catalyst] Based on the New Energy and Industrial Technology Development Organization (NEDO)'s "NEDO PEFC Cell Evaluation Analysis Protocol March 2022 Edition," IV measurements were performed using a fuel cell power generation evaluation device (manufactured by Chino) and an electronic load device (Kikusui Electronics PLZ164WA). Mass activity was calculated from the current density at 0.85 V and the amount of platinum loaded, and the initial activity was determined.
[0082] [Measurement of durability of MEA using platinum or platinum alloy supported carbon catalyst] Based on the potential cycle (load response) test method described in the New Energy and Industrial Technology Development Organization (NEDO)'s "NEDO PEFC Cell Evaluation Analysis Protocol March 2022 Edition," a load response simulated potential cycle test to accelerate the deterioration of platinum particles or platinum alloy particles in a platinum or platinum alloy supported carbon catalyst was conducted using a fuel cell power generation evaluation device (manufactured by Chino) and a potentiogalvanostat (PGSTAT128N manufactured by Metrohm).The mass activity after the durability test was calculated from the current density at 0.85 V and the amount of platinum supported after 30,000 cycles, and durability was evaluated.
[0083] At initial activation, 800Ag -1Above 300Ag -1 Over 800Ag -1 The activity after durability test was evaluated as 300Ag or less. -1 Above 100Ag -1 Over 300Ag -1 Less than 100Ag: 〇 -1 Less than this was rated as x.
[0084] [Table 2]
[0085] In Examples 1 to 6, the total weight of the second platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon is adjusted to 60 to 90% of the total weight of the first and second platinum particles or platinum alloy particles supported inside and outside the pores of the mesoporous carbon in two stages. The average particle size D1 of the platinum particles or platinum alloy particles supported inside the pores of the glass carbon is equal to or larger than the average particle size D2 of the platinum particles or platinum alloy particles supported outside the pores, and the initial mass activity is 300 Ag -1 and mass activity after 30,000 cycles is 100Ag -1 As described above, the catalyst had good initial activity and durability.
[0086] Comparative Example 1 is a platinum-supported carbon catalyst prepared by repeating only the intrapore support step twice, and the initial mass activity was 498Ag -1 While the initial activity was good, the mass activity after 30,000 cycles was 52Ag -1 The durability was also low.
[0087] Comparative Example 2 is a platinum-supported carbon catalyst prepared only by the liquid phase reduction method, which is an external support process, and the initial mass activity was 371Ag -1 While the initial activity was good, the mass activity after 30,000 cycles was 47Ag -1 The durability was also low.
Claims
1. A platinum or platinum alloy supported carbon catalyst in which platinum particles or platinum alloy particles are supported on mesoporous carbon, The platinum or platinum alloy loading rate in the catalyst is 30% or more and 70% or less based on the total weight of the catalyst, the total weight of the platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon is 60 to 90% based on the total weight of the platinum particles or platinum alloy particles; an average particle size D1 of platinum particles or platinum alloy particles supported within the pores of the mesoporous carbon is equal to or larger than an average particle size D2 of platinum particles or platinum alloy particles supported outside the pores of the mesoporous carbon; The average particle size D1 and the average particle size D2 are independently 2 nm or more and 8 nm or less, 1. A platinum or platinum alloy supported carbon catalyst.
2. The average particle size D1 is 2.5 nm or more and 8 nm or less, The average particle size D2 is 2.3 nm or more and 7.3 nm or less, D1 / D2 is 1.0 to 2.1; 2. The platinum or platinum alloy supported carbon catalyst according to claim 1.
3. A step of impregnating a mesoporous carbon support with an aqueous solution containing a platinum compound; a step of drying the mesoporous carbon support impregnated with the platinum compound-containing aqueous solution obtained in the above step under reduced pressure; a step of supporting platinum in the pores of the mesoporous carbon support, the step including a step of heat-treating the mesoporous carbon support dried under reduced pressure in a reducing atmosphere; a step of suspending the mesoporous carbon support having platinum supported in the pores after the step of supporting in the pores in an aqueous solution; mixing the suspension with an aqueous solution containing a platinum compound and a liquid containing a reducing agent to reduce the platinum compound; A method for producing a platinum-supported carbon catalyst comprising the steps of:
4. The in-pore supporting step includes: A step of adding and mixing an aqueous solution of dinitrodiamine platinum nitric acid to a mesoporous carbon support to obtain a platinum-supported carbon slurry; drying the obtained slurry at a predetermined temperature under reduced pressure to obtain a dry product; a step of reducing dinitrodiamine platinum by heat treatment in a reducing atmosphere; and a step of growing platinum particles by firing in an inert gas atmosphere (firing temperature T1). The outer pore supporting step includes: The mesoporous carbon support having platinum supported in the pores after the intrapore supporting step is suspended in an aqueous nitric acid solution; a step of heating and stirring the suspension, an aqueous dinitrodiamine platinum nitric acid solution, and a liquid containing L-ascorbic acid at 80° C. to 100° C. for 30 minutes to 5 hours to support platinum particles outside the pores of the carbon support; a step of filtering out the platinum-supported carbon having platinum particles supported outside the pores of the carbon support in the above step, washing the carbon support, drying the carbon support, and then calcining the carbon support in an inert gas atmosphere (calcination temperature T2) to grow platinum particles; The method for producing the platinum-supported carbon catalyst according to claim 3, comprising:
5. a step of adding an aqueous solution containing a compound of a metal to be alloyed with the platinum to the platinum-supported carbon catalyst and mixing them to obtain a slurry; and a step of heating and drying the obtained slurry under reduced pressure to obtain a dry solid.
5. The method for producing a platinum alloy-supported carbon catalyst according to claim 3, further comprising an alloying step of calcining the dried product in a reducing atmosphere and then calcining the dried product in an inert gas atmosphere to form an alloy.
6. By setting the firing temperature T1 and the firing temperature T2 to predetermined temperatures, 5. The method for producing a carbon catalyst carrying platinum or a platinum alloy according to claim 3, wherein the average particle diameter D1 of the platinum particles and the average particle diameter D2 of the platinum particles are controlled.
7. 10. A membrane electrode assembly for a polymer electrolyte fuel cell, comprising an electrode containing the platinum or platinum alloy supported on carbon catalyst according to claim 1.
8. 10. A polymer electrolyte fuel cell comprising the platinum or platinum alloy supported carbon catalyst according to claim 1 contained in an electrode of a membrane electrode assembly.
Citation Information
Patent Citations
Electrocatalyst for fuel cell and fuel cell
JP2004071253A
Production method of electrode catalyst
JP2006181541A
Air electrode catalyst layer and solid polymer fuel cell
JP2020155348A
Catalyst for fuel battery
JP2024006372A
Catalyst, catalyst layer, membrane electrode assembly, electrochemical device, and method for producing catalyst
WO2021059932A1